IMPLEMENTASI PENEGAKAN HUKUM KEPOLISIAN PADA PENGAMANAN UNJUK RASA YANG MENGAKIBATKAN TINDAKAN ANARKISDI KOTA TERNATE - Gunawan Hi Abas; Muh Yani Renwarin (JOURNAL OF LAW AND NATION, 2024)
The purpose of the study was to determine the implementation of police law enforcement in securing demonstrations that resulted in anarchic actions in the city of Ternate, and to determine what efforts and obstacles were in implementing the handling of demonstrations carried out by students that ended in anarchy. The study was conducted at the Ternate City Police. To achieve these objectives, the author used data collection techniques in the form of interviews and requested data from related parties. The research used was qualitative descriptive research, namely research conducted to obtain secondary data and materials related to research obtained from various sources. The results of this study indicate that the implementation of police law enforcement has three stages, namely persuasive, preventive and repressive. The three things that are most dominantly carried out by the police are persuasive and preventive in other words the approach in the form of negotiation, however, repressive actions can be carried out if the escalation of the protesters has led to unlawful acts. Then there are two things that hinder, namely: Internal factors, there are police officers in the field who do not understand the main duties of the police and acts of arrogance and overacting, then external factors, the protesters are out of control, the ratio of police officers is not balanced with protesters, then the community mixes with the protesters. In addition, field conditions are different from theoretical conditions, which makes it difficult to apply the principle of presumption of innocence to a demonstration that is running anarchically and the demonstrators behave brutally, making the principle of presumption of innocence difficult to apply.